Penerapan Pendekatan Saintifik Dengan Bantuan LKS-Induktif Dalam Pembelajaran Faktor-faktor Yang Mempengaruhi Laju Reaksi Pada Siswa Kelas XI SMAN-5 Palangka Raya Tahun Ajaran 2015/2016 - Christina Nopriani; Abudarin Abudarin; Akhmad Damsyik (FKIP Universitas Palangka Raya, 2018)
This study aims to: (1) describe student learning abilities; (2) describe the understanding of student concepts. This study involved 57 students of class XI Specialization in Mathematics and Natural Sciences in SMA Negeri 5 Palangka Raya. The instruments used were pretest and posttest question sheets, LKS-Inductive with a scientific approach, and interview guidelines. Data was collected through three stages, namely pretest, implementation of learning with a scientific approach assisted by LKS-Inductive, and posttest. Data were analyzed descriptively. The results showed that, the learning ability of students in learning with a scientific approach averaged 83.14% with details: (a) the ability to observe by 84.19%; (b) the ability to ask for 48.17%; (c) the ability to collect information at 89.39%; (d) the ability to associate is 96.09%; and (e) the ability to communicate at 87.25%. The ability of students to understand the concept of the factors that influence the rate of reaction in learning with a scientific approach using LKS-Inductive on average by 85.09%